Planificación estratégica y ejecución presupuestal en la gerencia regional de desarrollo agrario y riego Iquitos 2024 - Iparraguirre Marinho, Niki Jesus (2025)
The typically descriptive correlational study, with a quantitative approach, is designed to analyze the relationship between variables without manipulating them, observing phenomena as they occur in a cross-sectional manner. The Spearman correlation of 0.915 indicates a very strong and statistically significant correlation between the studied variables. The conclusions emphasize the significantly relational existence between the examined variables, which has important implications for optimizing the use of financial resources in management. The study provides solid evidence that a rigorous approach to strategic planning considerably improves budget execution in similar organizational contexts.